Involvement of multiple sodium ions in intestinal d-glucose transport. - Kaunitz, J D (1982)
Brush border membrane vesicles isolated from rabbit small intestine were used to measure the interactions between sodium and glucose transport with a rapid uptake technique. A plot of glucose uptake rate vs. increasing sodium concentration yielded a sigmoid curve. Hill analysis revealed a coefficient of 1.9 +/- 0.02 (+/- SEM), consistent with at least two sodium ions involved in glucose transport. Transport coupling was then measured directly with double-label experiments in which the uptakes of D-glucose and sodium were determined in the presence and absence of cotransported solute. At the earliest time point, the ratio of cosubstrate-dependent sodium transport to glucose transport was 3.2 +2- 0.7 (+/- SEM). We conclude that two or more sodium ions are coupled to glucose transport across the intestinal brush border membranes.